Evaluation of different moisture conservation practices on maize production and productivity in Dallomanna Districts of Bale Lowland Southeastern Ethiopia - Telila, Regassa Gosa; Naneso, Daniel Abagaja; Diriba, Mulugeta Eshetu; Defar, Tesfaye Ketema; Gemechu, Girma Getachew (Journal of Scientific Agriculture, 2024)
The in-situ moisture conservation and mulching are techniques that help retain moisture at the root zone, reduce evapotranspiration, and increase the time of infiltration for maize production. This study was focused on the evaluation of the best moisture conservation techniques in combination with mulching under rain-fed conditions for maize production in the study area. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Five treatments, namely, control (without structure and mulching), mulching, furrow ridge with open-ended furrow with mulching, furrow ridge with closed-ended furrow with mulching, and tied ridge with mulching, were compared for two consecutive seasons (2021 and 2022) in terms of soil moisture conservation and maize grain yield. The highest mean grain yield (6134.84 kg ha-1) and soil moisture content were recorded from the plot of T5 (Tied Ridge + Mulching). The result revealed that tied ridges with mulching showed better grain yield and conserved moisture over the others, followed by furrow ridges with close-ended furrows with mulching, respectively. Therefore, tied ridges with mulching as in-situ moisture conservation practices is an effective technique for storing moisture and increasing the time of infiltration as compared to other practices.